2022
DOI: 10.3389/fpubh.2022.1014351
|View full text |Cite
|
Sign up to set email alerts
|

Health shocks, basic medical insurance and common prosperity: Based on the analysis of rural middle-aged and elderly groups

Abstract: Health is a major part of human welfare. The index system of common prosperity was constructed for middle-aged and elderly people in rural areas. Besides, the impart of health shocks and rural basic medical insurance on common prosperity was explored. The data for this study came from China Health and Retirement Longitudinal Survey (CHARLS) in 2013, 2015, and 2018. The finding shows that health shocks hindered the improvement of the common prosperity of the middle-aged and elderly in rural areas, among which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Along with improving the economic condition of families, the government should also take measures to enhance the willingness of families to bear children, which can increase the number of family generations and diminish the pressure of long‐term care for family caregivers, thus contributing to the subjective well‐being of the elderly, especially the long‐lived (centenarian) elderly. Improved economic status and more children in the family are associated with the better health status of centenarians and the lower spillover of care needs 6,36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with improving the economic condition of families, the government should also take measures to enhance the willingness of families to bear children, which can increase the number of family generations and diminish the pressure of long‐term care for family caregivers, thus contributing to the subjective well‐being of the elderly, especially the long‐lived (centenarian) elderly. Improved economic status and more children in the family are associated with the better health status of centenarians and the lower spillover of care needs 6,36 …”
Section: Discussionmentioning
confidence: 99%
“…Improved economic status and more children in the family are associated with the better health status of centenarians and the lower spillover of care needs. 6,36 Intergenerational family support is a central component of aging, and has generated significant academic interest. In our study, the total intergenerational support score (consisting of financial, instrumental, and emotional support) for centenarians was 15 (Q1, Q3: 12, 15), with an overall high level of intergenerational support for centenarian families, which is consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Its rapid urbanization process has attracted a large number of young people from rural areas to migrate to cities, resulting in middle-aged and elderly people in rural areas becoming the main left-behind population ( Wang et al, 2022 ). Due to factors such as long-term agricultural activities, physical vulnerability and insufficient protection are common in this group of middle-aged and elderly people ( Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several scholars have stated that basic medical insurance positively affects health status (9-11), because medical insurance can reduce the price of medical services (12), offer more opportunities for medical care and higher-quality health services (13). However, other researchers have shown that basic medical insurance has little effect on the improvement of residents' health (14)(15)(16), the probable explanation lies in the fact that the current policy only focuses on the most basic issues, the finite reimbursement rates, and the limited protection for the health vulnerable population (17).…”
Section: Introductionmentioning
confidence: 99%